2009
DOI: 10.2139/ssrn.1520544
|View full text |Cite
|
Sign up to set email alerts
|

Reinvigorating Springfield’s Economy: Lessons from Resurgent Cities

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
12
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(15 citation statements)
references
References 7 publications
3
12
0
Order By: Relevance
“…Confirming the findings of others, Kodrzycki and Muñoz (2009b) found that having an especially large share of resident employment in manufacturing as of 1960 reduced the likelihood of resurgence. However, the current differences in manufacturing intensity and broader measures of industry mix between the resurgent and the nonresurgent cities were minimal.…”
Section: Turning Around the Economies Of Distressed Citiessupporting
confidence: 78%
See 4 more Smart Citations
“…Confirming the findings of others, Kodrzycki and Muñoz (2009b) found that having an especially large share of resident employment in manufacturing as of 1960 reduced the likelihood of resurgence. However, the current differences in manufacturing intensity and broader measures of industry mix between the resurgent and the nonresurgent cities were minimal.…”
Section: Turning Around the Economies Of Distressed Citiessupporting
confidence: 78%
“…Using case studies to detect commonalities among the resurgent cities, Kodrzycki and Muñoz (2009b) essentially concurred with the conclusions summarized in Wolman et al (2008). They found that the resurgent cities shared the following characteristics: leadership on the part of key institutions or individuals, collaboration among the various constituencies with a stake in economic development, long-term planning and periodic reevaluation of the plan, extensive infrastructure improvements, and development of new industries and city identities.…”
Section: Turning Around the Economies Of Distressed Citiessupporting
confidence: 75%
See 3 more Smart Citations